The Effectiveness of Using Films to Increase Entrepreneurial Interest and Learning Outcomes in Creative Product and Entrepreneurship Subjects - Rahmawati, Annisa; Widowati, Trisnani; Harlanu, Muhammad (Universitas Negeri Semarang, 2024)
This study aims to examine: 1) the difference in the increase of entrepreneurial interest among students using films as a teaching media in the Creative Products and Entrepreneurship subject, 2) the difference in the improvement of learning outcomes among students using films as a teaching media in the Creative Products and Entrepreneurship subject, and 3) the effectiveness of films in enhancing both entrepreneurial interest and learning outcomes in the Creative Products and Entrepreneurship subject. This research follows a quantitative approach with a quasi-experimental design. The study population consists of eleventh-grade students at SMKN 1 Salatiga from vocational programs in beauty, fashion, and culinary arts. A simple random sampling method was employed to select the sample. The experimental group was exposed to films as a teaching media, while the control group did not receive this treatment. Data on learning outcomes were gathered through written tests, and data on learning interest were obtained through closed questionnaires. The findings of this study are as follows: 1) a noticeable difference exists in the entrepreneurial interest between students who used films as a media and those who did not, 2) there is a significant difference in the improvement of learning outcomes between students who used films and those who did not, and 3) films have proven to be effective in improving both entrepreneurial interest and learning outcomes in the Creative Products and Entrepreneurship subject at SMKN 1 Salatiga.